SaÃ¢â¬â¢Unine String Orchestra, Orkes Geseknya Indonesia - Rachmawanti, Ranti - (PANGGUNG, 2012)
ABSTRACTÃÂ This article explains the result of SaÃ¢â¬â¢Unine String Orchestra as one of Indonesian orchestras in popular culture. Main idea of this research is to uncover and describe the characteristic, func- tion, and role of SaÃ¢â¬â¢Unine String Orchestra within the popular culture in Indonesia. This research used qualitative method with ethnographical approaches to identify all facts that discovered during research. The conclusions of this research show that SaÃ¢â¬â¢Unine String Orchestra moves in two ways, there are; the idealism which had a vision to create a real Indonesian string orchestra and a part of music industry. At the end, these two ways are connected to each other because of the earnings of those. Music industry becomes a support factor which create the idealism of SaÃ¢â¬â¢Unine String Or- chestra to be an Indonesian String Orchestra.ÃÂ Keywords: String Orchestra, Music, Popular Culture.ÃÂ